67.0k views
1 vote
Prove that:

a.) [csc^2(x)] * [tan^2(x)] -1 = [tan^2 (x)]

b.) Sec(x)/Cos(x) - tan(x)/cot(x) = 1

Show all your work for both the equations!

User Jala
by
6.9k points

1 Answer

3 votes
a.)


\csc^2(x) \tan^2 (x)- 1 = \tan^2(x)

Use the identities
\csc x = 1 / \sin x and
\tan x = \sin x / \cos x on the left-hand side


\begin{aligned} \text{LHS} &= \csc^2(x) \tan^2 (x)- 1 \\ &= (1)/(\sin^2 (x)) \cdot (\sin^2 (x))/(\cos^2 (x)) - 1 \\ &= (1)/(\cos^2 (x)) - 1 \end{aligned}

Make 1 have a common denominator to allow for fraction subtraction
Multiply the numerator and denominator of 1 by cos^2 x


\begin{aligned} \text{LHS} &= (1)/(\cos^2 (x)) - 1 \cdot \tfrac{\cos^2 (x)}{\cos^2 (x)} \\ &= (1)/(\cos^2 (x)) - (\cos^2 (x))/(\cos^2 (x)) \\ &= (1 - \cos^2 x)/(\cos^2 (x)) \end{aligned}

Use Pythagorean identity for the numerator.

If
\sin^2 (x) + \cos^2(x) = 1 then subtracting both sides by
\cos^2 (x) yields
\sin^2(x) = 1 - \cos^2(x). We can substitute that into the numerator


\begin{aligned} \text{LHS} &= (1 - \cos^2 (x))/(\cos^2 (x)) \\ &= (\sin^2 (x))/(\cos^2 (x)) \\ &= \tan^2 (x) && \text{Since } \tan x = \tfrac{\sin x }{\cos x} \\ &= \text{RHS} \end{aligned}

======

b.)


(\sec(x))/(\cos(x)) - (\tan(x))/(\cot(x)) = 1

For the left-hand side:
By definition,
\sec(x) = 1/\cos(x) and
\tan (x) = 1/\cot (x)


\begin{aligned} \text{LHS} &= (\sec(x))/(\cos(x)) - (\tan(x))/(\cot(x)) \\ &= ( (1)/(\cos(x)) )/(\cos(x)) - ((1)/(\cot(x)))/(\cot(x)) \\ &= (1)/(\cos^2 (x)) - (1)/(\cot^2(x)) \end{aligned}

Since
\cot (x) = \cos (x) / \sin (x)


\begin{aligned} \text{LHS} &= (1)/(\cos^2 (x)) - (1)/((\cos^2(x))/(\sin^2(x)) ) \\ &= (1)/(\cos^2 (x)) -(\sin^2(x))/(\cos^2(x)) \\ &= (1 - \sin^2(x))/(\cos^2 (x)) \end{aligned}

Using Pythagorean identity,
\cos^2(x) = 1 - \sin^2(x) so


\begin{aligned} \text{LHS} &= (\cos^2(x))/(\cos^2 (x)) \\ &= 1 \\ &= \text{RHS} \end{aligned}
Prove that: a.) [csc^2(x)] * [tan^2(x)] -1 = [tan^2 (x)] b.) Sec(x)/Cos(x) - tan(x-example-1
User Kevlar
by
5.5k points